Rose Gold Financing Analysis to Reduce Community Dependence on Moneylender Services (Case Study of the Nurul Ikhsan Lengaluh Mosque) - Ismayadi, Ismayadi; Juwita, Listiana (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research was motivated by the phenomenon of loan sharks which is often found in society today, then the NTB government provided a solution to reduce people's dependence on loan shark services by channeling financing using qardh contracts using the concept of mosque-based empowerment. This research aims to find out the impact of Mawar Emas financing with the mosque empowerment concept provided by the government to the community to minimize their dependence on moneylenders. In using the writing method, the researcher used a qualitative and descriptive method with a phenomenological approach. The data collection techniques used were observation, interviews, questionnaires and documentation. Data processing is carried out by selecting and sorting data obtained through observation, interviews, questionnaires and documentation, presenting all the selected data and then analyzing it and producing conclusions. Based on the results of research conducted by researchers, it shows that the Mawar Emas financing program to minimize community dependency on loan shark services at the Nurul Ikhsan Lengaluh Mosque has not been completely able to free customers from loan shark services, however the community feels empowered by the business assistance provided by the Mawar financing program. Gold.